Kompetensi Interkultural Pengajaran Bahasa Arab sebagai Bahasa Asing pada Jenjang Madrasah Aliyah - Muhammad Yusuf (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2020)
The intercultural aspect is an important component of teaching Arabic in Indonesia. That is because cross-cultural understanding is the basis for learners to be able to communicate and interact in Arabic effectively and efficiently. This paper examines how the concept of intercultural competence in teaching Arabic at the level of Madrasah Aliyah. Academic problems are read using the literature method and analyzed using content analysis. This study formulates that intercultural competence in teaching Arabic at the Madrasah Aliyah level consists of students' knowledge of the language as a cultural phenomenon of Arab society, student awareness of cultural distinction and culture of Arab society, and sensitivity of students to these differences. In the framework of obtaining intercultural competencies, the learning process must be constructive, interactive, connective, reflective, and responsive. While teaching evaluation can be done using oral tests or by observation, project-based assessment, portfolio, or peer assessment. In addition, the qualifications of a teacher besides being professional must also be able to understand the culture of Arab and Islamic society to further assess, be innovative, and be able to conduct constructive studies of the cultural and linguistic aspects of Arab and Indonesian society. Keywords: Intercultural Competence, Foreign Language Pedagogy, Arabic Language, Madrasah Aliyah